Andean entrepreneurs : Otavalo merchants and musicians in the global arena - Meisch, Lynn, 1945- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2002)
Native to a high valley in the Andes of Ecuador, the Otavalos are an indigenous people whose handcrafted textiles and traditional music are now sold in countries around the globe.